The Dilemmatic Relationship Between Indonesia’s Government and Individuals in the Case of Runaway First or #KaburAjaDulu - Fachrie, Muhammad; Wahyudi, Herry (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2025)
This research analyzes the dilemmatic relationship of Indonesia’s runaway first or #KaburAjaDulu. In this phenomenon, individuals used social media Twitter to make a protest toward Indonesia’s government about runaway first, which they did not want to return to Indonesia after finishing their education in abroad. It has attracted public attention both domestic and international because it has raised a public concern about situation and condition in Indonesia. While several articles explained the causes of this phenomenon, the comprehensive understanding of the cause of it is yet nonexistent in literature. Therefore, this research aims to make clear of relational cause of this phenomenon. By using qualitative method and stag hunt game theory, this research collects data from book, journal, online news, publication and other data, organize and analyze them, and then result findings. As a result, this research finds that the dilemmatic relationship between government and individuals or scholars is caused by the mutual distrust and uncommitted actions from both of government and individuals. One the one hand, the government result in distrust in creating proper working environment for scholars. On the other hand, several scholars refused to accept status quo of the working environment in Indonesia due to more promising opportunities abroad.